2016
DOI: 10.1159/000442152
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation with an Internally Cooled Electrode for Twin Reversed Arterial Perfusion Sequence

Abstract: Objective: The study aims to evaluate the efficacy of radiofrequency ablation (RFA) with an internally cooled electrode for twin reversed arterial perfusion (TRAP) sequence. Methods: From April 2008 through December 2014, we retrospectively reviewed all patients who underwent RFA with an internally cooled electrode for TRAP sequence at 3 tertiary referral centers in Japan. Results: Twenty-five monochorionic diamniotic twin pregnancies underwent RFA with an internally cooled electrode for TRAP sequence at 16-27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Kumar et al once reported two cases of presumed thermal injury to the cotwin's lower limb and scalp, respectively, which may be due to one of the 110°C RFA needle tines directly contacting the cotwin . Unlike the most widely used expandable needle electrodes, the MWA antenna is similar to the internally cooled electrodes in that each has one tip without tines, which makes them easy to manipulate and position in the target fetus . Thus, the MWA antenna will not contact the cotwin; this benefit may make MWA safer than RFA using expandable needle electrodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al once reported two cases of presumed thermal injury to the cotwin's lower limb and scalp, respectively, which may be due to one of the 110°C RFA needle tines directly contacting the cotwin . Unlike the most widely used expandable needle electrodes, the MWA antenna is similar to the internally cooled electrodes in that each has one tip without tines, which makes them easy to manipulate and position in the target fetus . Thus, the MWA antenna will not contact the cotwin; this benefit may make MWA safer than RFA using expandable needle electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Unlike the most widely used expandable needle electrodes, the MWA antenna is similar to the internally cooled electrodes in that each has one tip without tines, which makes them easy to manipulate and position in the target fetus. 6,7,21 Thus, the MWA antenna will not contact the cotwin; this benefit may make MWA safer than RFA using expandable needle electrodes. due to its decreased susceptibility to the heat-sink effect.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival rate was 85%, and the mean gestational age at delivery was 37 weeks for the pump twins. The other study also reported good outcomes of RFA treatment for TRAP sequence, with a survival rate of 88% [57]. Although reports of RFA treatment for TRAP sequence are limited, RFA is thought to be a useful treatment option for TRAP sequence after 15 weeks' gestation.…”
Section: Radiofrequency Ablationmentioning
confidence: 88%
“…Lee et al [55] reported the North American Fetal Therapy Network registry data of RFA treatment for TRAP sequence and showed the 80% survival rate. Two studies of RFA for TRAP sequence were performed in Japan [56,57]. We reported the outcomes of 40 cases of TRAP sequence treated with RFA, which is the largest single-center study [56].…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…The primary indications for RFA are TRAPs and other lethal foetal anomalies [14]. After RFA, the overall survival rate of the co-twin in TRAPs is determined to be at 75.0-92% [8][9][10][15][16][17][18][19], but it varies in other anomalies, ranging 33-92.3% [8,13,15]. RFA is also recommended for sIUGR in which laser may not be a desirable choice for large vessel anastomosis [5,20,21].…”
Section: Introductionmentioning
confidence: 99%